Calle 54 - Trueba, Fernando 1955 (Miramax Home Entertainment, 2001)
A musical journey that captures the heart and soul of an entire culture. The sound that pulsates in hot backstreet clubs and recording studios. From Miami to Havana, the Bronx to Andalusia. A series of performances that reveal how these great Latin heroes use their extraordinary musical talent as a vehicle for storytelling, protest, sexuality and, above all, the celebration of life.